Kuntowijoyo and Prophetic Social Sciences: Integrating Revelation and Modern Methodology for Ethical Social Transformation - Mhd. Maulana Ansori; Haris Riadi; Rizki Arzi Wahyudha; Hazani Hazani; Suheryeni Suheryeni (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This article discusses Kuntowijoyo's thoughts on Prophetic Social Science as an offer of a scientific paradigm that integrates revelation, prophetic values, and modern social science methodology. Prophetic Social Science is constructed through three main dimensions humanization, liberation, and transcendence, which are based on QS. Ali 'Imran 110 as a normative foundation. This study traces Kuntowijoyo's intellectual biography, the epistemological foundation of his ideas, the methodological tools he formulated, and their application and relevance in the context of contemporary Indonesian science and social life. Through descriptive-qualitative analysis, this article shows that Prophetic Social Science has made a significant contribution to developing emancipatory and value-oriented social science, although it continues to face criticism regarding the operationalization of the concept, the tension between revelation and scientific objectivity, and the methodology of problems in research practice. These findings confirm that Prophetic Social Science is an important intellectual project in the effort to build a social science that not only explains reality but also transforms it ethically and transcendentally.